Reinsertion of traumatic avulsion of the superficial and deep flexor tendons of the little finger using the pull-out technique - Henrique Mansur; Cesar Gonçalves; Isnar Castro; João Luiz Durigan (Revista Brasileira de Cirurgia Plástica)
Simultaneous closed traumatic avulsion of both the deep flexor tendon and the superficial flexor tendon of the fingers is rare, and only nine cases have been reported in the literature since 1984. Several surgical procedures for repairing flexor tendon lesions have been described, but there is no consensus on the best approach to reinsert the tendon. We report the case of a patient who suffered a traumatic avulsion of the superficial flexor tendon and the deep flexor tendon of the fifth finger, which was surgically treated using the pull-out technique.